Recruiting, training and retaining competent overseas English language teachers for private language teaching organisations in China. - Zhang, Yan (2015)
Recruitment of overseas English teachers is becoming a tendency in face of business strategies and a widening demand-supply gap. While, some private and small LTOs in China lack of the experience and investment just take advantage of generous salary and benefits to attract foreign teachers. Especially, when approaching term time, they usually lower the requirements on teachers, which tend to cause many potential problems. Theoretical background in recruitment process and work motivation are identified in the literature. Two research questions are developed i.e., (i) extent to which private LTOs in China have adopted and implemented the recruitment practices recommended in the literature to recruit the overseas English teachers who best fit with organization culture and job demands (ii) extent to which overseas English teachers’ motivation and needs are being met. The author used triangulation research method interrelating qualitative and quantitative data to answer the research questions. The results revealed that LTOs partially adopted recruitment practices indentified in the literature on account of cost and human resource constraints. Further, lack of ongoing support as well as job training would contribute to high turnover rate. These findings have practical implications for educational organizations facing similar situations.